Tingkat Pengetahuan Atlet Gulat Popda Kabupaten Tanah Laut Terhadap Peraturan Pertandingan Gaya Bebas Terbaru - Samudra, Imam; Anggara, Norma; Fauzan, Lazuardy Akbar (Jurnal Porkes, 2025)
The purpose of this study is to measure athletes' understanding of the latest regulations, so that the results can be useful for athletes in increasing their awareness of the importance of understanding regulations, for coaches as evaluation material for coaching, and for sports coaches as consideration in organizing more structured training on regulations. This research uses a quantitative descriptive method, which is an approach that focuses on the presentation and interpretation of an object according to its actual conditions without any data manipulation. The data collection technique uses a questionnaire. The sample in this study consisted of 16 freestyle wrestling athletes from Tanah Laut Regency participating in the 2025 POPDA. Based on the results of the study on the level of knowledge of the 2025 POPDA freestyle wrestling athletes from Tanah Laut Regency regarding the latest freestyle competition rules, it was found that most athletes had a good understanding. A total of 12 athletes (75%) were in the high knowledge category, indicating that the dissemination of information and training on the rules had been quite effective. However, there were still 2 athletes whose knowledge was classified as low (12.5%) and 2 athletes whose knowledge was very low (12.5%). The conclusion is that the level of knowledge of Tanah Laut Regency POPDA freestyle wrestling athletes regarding the latest freestyle regulations is good, with the majority of athletes falling into the high category.